2019
DOI: 10.18609/cgti.2019.137
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the clarification of industrial scale viral vector culture for gene therapy

Abstract: Viral-based vector systems such as lentivirus (LV) and adeno-associated virus (AAV) are widely used and show great potential for delivery of genetic material to target cells in gene therapy. Downstream processing of LV and AAV offers its own unique challenges to generate clinical products of high titer, high potency, and high purity. For AAV, downstream challenges include the undesired production of empty capsids, and the process typically requires a cell lysis step, which generates a significant amount of hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 0 publications
1
13
0
Order By: Relevance
“…In addition to affinity chromatography, ion exchange chromatography has been extensively explored as an initial capture step. Due to the net charge on the surface of the capsid at a wide range of pH (pI 5.9-6.3; Qu, Wang, Wu, & Xu, 2015), ion exchange chromatography can work as a capture step but often cannot be highly selective due to the number of charged impurities present in the capture load. This results in the need for multiple purification steps.…”
Section: Purification Of Aav Vectors Through Capture Chromatographymentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to affinity chromatography, ion exchange chromatography has been extensively explored as an initial capture step. Due to the net charge on the surface of the capsid at a wide range of pH (pI 5.9-6.3; Qu, Wang, Wu, & Xu, 2015), ion exchange chromatography can work as a capture step but often cannot be highly selective due to the number of charged impurities present in the capture load. This results in the need for multiple purification steps.…”
Section: Purification Of Aav Vectors Through Capture Chromatographymentioning
confidence: 99%
“…The packaged DNA is believed to interact with the surface proteins of the capsid and change the net charge present on the capsid surface. Based on literature, the mean calculated pI value of all the AAV's empty capsids is estimated to be 6.3 and full capsids estimated to be 5.9 (Qu et al, 2015), which enables this separation, although exact values will vary based on serotype. Impurities like HCP and DNA have both a large size and pI difference that also allows for separation using ion-exchange based chromatography (IEX) due to the difference in surface charge at given conditions.…”
Section: Purification Of Aav Vectors Through Polishing Chromatographymentioning
confidence: 99%
See 1 more Smart Citation
“…Filtration techniques, which are effective and scalable, dominate initial clarification, with disposable systems offering simplified cleaning and validation. The use of cascading filters, whereby the feed is filtered with progressively finer filters can prevent premature fouling of the end filter that may result in titre loss due to vector exclusion and extended process times due to reduced flux [ 182 , 183 ]. The choice of filter impacts the efficiency of the clarification step.…”
Section: Downstream Processing Of Lentiviral Vectorsmentioning
confidence: 99%
“…There are also implications for the early part of the downstream process; a recent study we performed has shown that different clarification strategies are required depending on whether the virus is manufactured in adherent or suspension format [1].…”
mentioning
confidence: 99%